Students Mathematical Communication Skills in Solving Contextual Problems of Three Dimensional Figures at Junior High School Level - Aribah, Amanda Kurnia Zarh; Swastika, Annisa (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2024)
The purpose of this study was to describe the mathematical communication skills of students in solving three-dimensional space problems based on contextual problems. The research was carried out at SMP Muhammadiyah 7 Bayat, Klaten, Jawa Tengah. The study utilized a descriptive qualitative research method.  Data was collected through written test questions and interviews. The subject of this research consist of three classes of students from grade. The data analysis techniques used were data reduction, data presentation, and drawing conclusions. The findings indicate that not all students met the indicators of mathematical communication ability. Subject 1 has met all the indicators of mathematical communication skills. Subject 2 had difficulty mentioning the information contained in the problem, as required by the first indicator of mathematical communication ability. In contrast, subject 3 had difficulty fulfilling the second and third indicators of mathematical communication, which are the ability to understand, interpret, and evaluate mathematical ideas, and the ability to use mathematical terms, notations, and structures to present ideas and describe relationships with situation models.